Peak power output predicts rowing ergometer performance in elite male rowers - Bourdin, M.; Messonnier, L.; Hager, J.-P.; Lacour, J.-R. (International Journal of Sports Medicine, 2004)
The aim of the present study was to test the hypothesis that peak power output (Ppeak) sustained during maximal incremental testing would be an overall index of rowing ergometer performance over 2000 m (P2000), and to study the influence of selected physiological variables on Ppeak. A group of 54 highly trained rowers (31 heavyweight [HW] and 23 lightweight [LW] rowers) was studied. Body mass, maximal oxygen uptake (V·O2max), oxygen consumption corresponding to a blood lactate of 4 mmol · l-1 expressed in percentage of V·O2max (V·O2La4 %), and rowing gross efficiency (RGE) were also determined during the incremental test. In the whole group Ppeak was the best predictor of P2000 (r = 0.92, p < 0.0001). Body mass (r = 0.65, p < 0.0001), V·O2max (r = 0.84, p < 0.0001), V·O2La4 % (r = 0.49, p < 0.0001) and RGE (r = 0.35, p < 0.01) were significantly correlated with P2000 as well. To take the influence of body mass into account, V·O2max was related to kg0.57. Ppeak was significantly related to body mass (r = 0.56, p < 0.0001), V·O2max · kg-0.57 (r = 0.63, p < 0.0001), V·O2La4 % (r = 0.45, p < 0.001) and RGE (r = 0.34, p < 0.05). Multiple regression analysis indicated that the above parameters taken together explained 82.8 % of Ppeak variation in the whole group. It was also demonstrated that Ppeak was the best predictor of P2000 when LW and HW groups were considered separately. It was concluded that, by integrating the main physiological factors of performance, Ppeak is an overall index of physiological rowing capacity and rowing efficiency in heterogeneous as well as in homogeneous groups. It presents the further advantage of being easily measured in the field.